2013
DOI: 10.30539/iraqijvm.v37i2.275
|View full text |Cite
|
Sign up to set email alerts
|

Ecto and Endo Parasites Prevalence in Domestic Chickens in Sulaimani Region

Abstract: The study was conducted on 65 local adult chickens (Gallus domesticus) to investigate  macro - and microscopically presence of external and internal parasites and their prevalence in Sulaimani region-Kurdistan/Iraq from May to July 2012. Results showed that 90.77 % out of total examined chickens were infested with ecto-parasites, out of that 81.36 % (48/59) were infested with lice such as (Menacanthus  stramineus, Goniocotes  gallinae, Menopon  gallinae, Goniodes  gigas, Cuclotogaster  heterographus ) and 62.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The Jember district of East Java province study showed that helminths infection prevalence in laying chickens is mostly caused by Ascaridia galli (60%) (Kusuma et al 2021). However, Molla et al (2012) in Ethiopia reported that the prevalence of helminths infections in free-range chickens reached 79.62%, and Abdullah and Mohammed (2013) study at Sulaimani Region, Iraq, found that the common endo-parasite was Heterakis gallinarum 81%. Various helminths species were commonly found in indigenous chickens raised in backyards in Northern Thailand, i.e., H. gallinarum, A. galli, and Capillaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…The Jember district of East Java province study showed that helminths infection prevalence in laying chickens is mostly caused by Ascaridia galli (60%) (Kusuma et al 2021). However, Molla et al (2012) in Ethiopia reported that the prevalence of helminths infections in free-range chickens reached 79.62%, and Abdullah and Mohammed (2013) study at Sulaimani Region, Iraq, found that the common endo-parasite was Heterakis gallinarum 81%. Various helminths species were commonly found in indigenous chickens raised in backyards in Northern Thailand, i.e., H. gallinarum, A. galli, and Capillaria spp.…”
Section: Introductionmentioning
confidence: 99%